Substitutional doping of Li in Li[LixNi0.7−xCo0.2Fe0.1]O2 cathode materials and the effects on structure, oxidation states and electrochemical processes. (4th July 2018) - Kamarulzaman, Norlida; Mokhtar, Nurul Atikah Mohd; Kasim, Muhd Firdaus; Azahidi, Azira
Abstract: Substitutional doping of lithium also known as overlithiation, is one of methods widely used to improve performance of cathode material in Li-ion batteries. It is found that all prepared overlithiated samples, that is, Li[Lix Ni0.7−x Co0.2 Fe0.1 ]O2 where x = 0.05, 0.1 and 0.15, show improved performance in terms of both specific capacities and cycling. The best of the materials exhibits an 18% increase in the first cycle and only an 8% capacity fading at the 50th cycle. Although this phenomenon of improved electrochemical characteristics is known, the scientific reasoning behind it is not that well understood. In this work, analyzing the materials from the aspects of crystal structure, crystallite size and oxidation states help contribute in the understanding of the fundamental causes of the improvement of the electrochemical behaviour of the overlithiated cathode materials.